2019
DOI: 10.1101/724880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pedigree-based measurement of thede novomutation rate in the gray mouse lemur reveals a high mutation rate, few mutations in CpG sites, and a weak sex bias

Abstract: Pedigree-based measurement of the de novo mutation rate in the gray mouse lemur 3 reveals a high mutation rate, few mutations in CpG sites, and a weak sex bias 4 5 Abstract 1617 Spontaneous germline mutations are the raw material on which evolution acts and knowledge 18 of their frequency and genomic distribution is therefore crucial for understanding how evolution 19 operates at both long and short timescales. At present, the rate and spectrum of de novo 20 mutations have been directly characterized in only a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Assuming the average parental age in our sample (3.8 years) is representative of the average age of reproduction in the cat, we estimate a per-year mutation rate of 2.2 × 10 -9 per bp. This is much higher than the human rate of 0.43 × 10 -9 per bp per year (Jónsson et al 2017), or the per-year rate from any reported primate (Besenbacher et al 2019;Campbell et al 2020;Wang et al 2020;Wu et al 2020). This higher rate is driven by the similar number of mutations at puberty, but a much shorter generation time in the cat.…”
Section: Mutation Rate In the Domestic Catmentioning
confidence: 69%
“…Assuming the average parental age in our sample (3.8 years) is representative of the average age of reproduction in the cat, we estimate a per-year mutation rate of 2.2 × 10 -9 per bp. This is much higher than the human rate of 0.43 × 10 -9 per bp per year (Jónsson et al 2017), or the per-year rate from any reported primate (Besenbacher et al 2019;Campbell et al 2020;Wang et al 2020;Wu et al 2020). This higher rate is driven by the similar number of mutations at puberty, but a much shorter generation time in the cat.…”
Section: Mutation Rate In the Domestic Catmentioning
confidence: 69%
“…Several factors likely contribute to this large difference. First, the MSC estimate uses a de novo mutation rate sampled from a distribution based on available pedigree-based mutation rates in primates, including mouse lemurs (Campbell et al, 2019). This rate is nearly two-fold higher than the estimated substitution rate for M. murinus (dos Reis et al, 2018).…”
Section: Cryptic Speciation In Mouse Lemursmentioning
confidence: 99%
“…Up until now, the germline mutation rate has only been estimated using pedigrees in a few non-human primate species, including chimpanzee ( Pan troglodytes ) [ 18 , 26 , 27 ], gorilla ( Gorilla gorilla ) [ 27 ], orangutan ( Pongo abelii ) [ 27 ], African green monkey ( Chlorocebus sabaeus ) [ 28 ], owl monkey ( Aotus nancymaae ) [ 19 ], the baboon ( Papio anubis ) [ 29 ], and recently rhesus macaque ( Macaca mulatta ) [ 30 ]. The mutation rate of grey mouse lemur ( Microcebus murinus ) [ 31 ] has also been estimated in preprinted studies. To precisely call de novo mutations in the offspring, collecting and comparing the genomic information of the pedigrees is the first essential step for detecting mutations only present in offspring but not in either parent.…”
Section: Introductionmentioning
confidence: 99%